A política de regularização fundiária e reforma agrária: o PAE nas ilhas do Pará - MAIA, Rosane de Oliveira Martins (Universidade Federal do Pará, 2012)
This thesis studies the Land Reform and Land Settlement Policy in the Amazon region, from the Second National Plan for Land Reform (PNRA II), which inserted the traditional riverine populations in the whole of its audience. We focus on the analysis of settlement projects in the municipalities of the Lower Tocantins Microregion islands (State of Pará). The project was conducted by a task force formed by INCRA (The National Institute of Colonization and Agrarian Reform) and SPU (National Secretary of the Federal Government Heritage). However, the proposed use and democratization of land ownership, which allows land to be secured for the riverine populations, was not strategically planned and prioritized by government institutions. Through the analysis of the decision-making process, the action plans of some institutions, the perceptions of data collection by the associations of the settled people, and the outcome of elections from 2000 to 2010, we conclude that the settlement projects were intensely carried out in a disorderly fashion, aiming to respond to the Lula administration’s land reforming indices in order to create a positive impact on election results which were essential to maintain the governing political system.